(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article touches upon the accreditation systems for higher education of the Republic of Armenia (RA) and the Russian Federation (RF). Evolutions and development perspectives of the accreditation system of RA and RF have been analyzed, and a comparative analysis has been conducted. Generalizing the practice of accreditation in the system of higher education in RA and RF, we note the basic differences: 1. Armenian accreditation agency - National Center for Professional Education Quality Assurance (ANQA) is functionally independent. Russian accreditation agency - National Accreditation Agency (NAA) is a governmental structure. 2. The model of state accreditation operating in the RA functions in the form of mandatory institutional accreditation and voluntary program accreditation, whereas the Russian Federation is practicing program accreditation. 3. In contrast to the Republic of Armenia, where only the institute of state accreditation operates with the only accreditation agency ANQA, in the Russian Federation, the institutes of public and professional-public accreditation are also developed, and the most famous corresponding accreditation agencies, The Agency for Quality Assurance in Higher Education and Career Development ( AKKORK ) and the National Accreditation Center are introduced along with NAA in European Association for Quality Assurance in Higher Education (ENQA) and are included, in contrast to the NAA, into the register, The European Quality Assurance Register for Higher Education (EQAR). Note that ANQA also has membership in ENQA and is included in the EQAR register. 133 4. There are numerous differences in the procedure for conducting an accreditation expertise. The RF does not provide the institution of appeal against decisions of state accreditation either. 5. The higher education accreditation system of the RA is based on the compliance with Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG). The situation is different in the model of state accreditation of the Russian Federation. Although the quality assurance systems of the RA and the Russian Federation differ in the forms of organization of the respective structures and in the chosen models of accreditation, the agreement on cooperation and interaction between NAA and ANQA signed in June 2016 can serve as a basis for further harmonization of the accreditation systems of the RA and the RF.